Analytical Study of Geometric Parameter Effect on the Behavior of Horizontally Curved Reinforced Concrete Deep Beam. (17th May 2022) - Kenea, Goshu
Abstract : Nonlinear finite element simulation was once employed to look into the behavior of horizontally curved reinforced concrete deep beams under concentrated load at its mid-span. The study focused on the parametric impact of span length-to-depth (L/D) and span length-to-radius (L/R) ratios. In addition, the effect of longitudinal and spacing of shear reinforcement on the behavior of the beam has been investigated. The study considered sixteen beam specimens. Three of these specimens were straight beams as a control, and others were curved beams. The concrete-damaged plasticity model has been used to model the beam with C-25 grade concrete and steel reinforcements having diameters of ∅ 4 mm, ∅ 10 mm, and ∅ 12 mm with 568 MPa, 596 MPa, and 643 MPa steel grade, respectively. Reduced twenty-noded brick (C3D20 R) and two-noded (T3D2) elements have been used for modeling concrete and steel, respectively. The ultimate load capacity, the strain distribution, the load-deflection curve, and the load-twisting curve are the main outputs of the FE simulation. The study confirmed a considerable decrease in load-carrying capacity by up to 8.74% and 27.95% as the (L/R) ratio increased from 0 to 1.57 and the L/D ratio increased from 2.4 to 3, respectively. However, as the longitudinal steel ratio increased from 0.02042 to 0.02608 and the spacing of shear reinforcement decreased from 100 mm to 50 mm, the ultimate load capacity is increased up to 9.28% and 4.3%, respectively. Sensitivity evaluation was also conducted to see how much the independent variables (L/D ratio, L/R ratio, longitudinal bar ratio, and spacing transverse reinforcement) affect the dependent parameter (ultimate load capacity).